Double-triangular flap for reconstruction of a circular skin defect in the central frontal region - Georgi Tchernev; Simona Kordeva (PAGEPress Publications, 2024)
A 75-year-old female presented to the dermatology department with primary complaints of a tumor formation located in the center of the forehead, above the eyebrows. The adjacent skin was slightly sun damaged but no signs of surgical scars or malignancy were noted. A clinical diagnosis of basal cell carcinoma was established, and the patient was recommended surgical excision under local anesthesia.